ANALYSIS OF LINGUISTIC FEATURES OF BEAUTY PRODUCT ADVERTISEMENTS IN COSMOPOLITAN MAGAZINE: A CRITICAL DISCOURSE ANALYSIS - Renaldo, Zainal Arifin (Universitas PGRI Sumatera Barat, 2017)
This research aims at exploring the linguistic features employed by advertisers in Cosmopolitan Magazine beauty product advertisements. The study mainly focuses on the use of language in beauty product advertisements and the strategies employed by the advertisers in shaping the ideal concept of women’s beauty. This research is conducted under the theory of Critical Discourse Analysis proposed by Fairclough that focuses on a conception of discourse as text (micro level), discourse practice (meso level) and sociocultural practice (macro level). Its aim is to explore the relationships among language, ideology and power and to find out how advertisers persuade the women to buy their products. The result shows that there are some linguistic features employed by the advertisers i.e. positive and negative adjective, pronouns, imperatives, and modality. Meanwhile the strategies employed are positive-self representation, irrational representation, celebrity endorsement, and clinical test proof